TINDAK TUTUR EKPRESIF MENGELUH PADA FILM TAKSI (1990) - Nur Rokhim (Translation and Linguistics (Transling), 2023)
Abstract: This study aims to find out expressive speech acts complaining about Trosborg's theory, (1995) which is in the film Taksi (1990). The method in this study uses descriptive qualitative. The source of the data in this study is the utterances of all the characters in the film Taksi (1990). The results in this study showed that the speech act of complaining was the highest, namely showing criticism by 42%, followed by the speech act of complaining which showed annoyance of 36%, then the last, the smallest, was the speech act of complaining which showed indifference by 22%.Keywords: Speech act, expressive, complain, film.